Neutrosophic Analysis of Strategies to Improve Productivity in an Restaurant Chain - Efrén Gonzalo Montenegro Cueva; Milena Alejandra Napa Alcívar (Neutrosophic Sets and Systems)
a neutrosophic framework. The research focused on identifying effective strategies to optimize processes and addressing specific challenges such as staff turnover and compensation management. The TOPSIS method, combined with bipolar neutrosophic numbers, was employed to evaluate a group of strategies based on high-impact criteria. The results highlighted the implementation of economic incentives, training and retention programs, and performance management systems as the most effective alternatives. In contrast, internal communication campaigns and flexible schedules were found to be less prioritized. The research demonstrated the utility of neutrosophic logic in handling uncertainty and ambiguity, offering a replicable model for decision-making in complex business sectors.